Educação ambiental crítica para a convivência com/no semiárido: o processo de formação continuada de docentes no município de São José dos Cordeiros-PB - Machado, Myller Gomes (2021)
The present research entitled continuing education of teachers in Environmental Education (EE) Critical contextualized for living with/in the Semiarid Region was developed in the context of the Semiarid Region and has the general objective of unveiling the theoretical and methodological knowledge for a critical-reflective practice based on the formation continued in Critical EE. Thus, we defend the thesis that the continued formation in Critical EE for living with/in the Semiarid region provides teachers with theoretical and methodological basis for a critical-reflexive practice. In the methodology, we use qualitative research as an approach with methodological assumptions of critical-collaborative action research as a way to seek a think-act based on continuing education with 13 teachers from public schools in the city of São José dos Cordeiros, Semi-arid of Paraíba. Data were constructed from questionnaires (pre and post-training) and participant observation carried out during the development of pedagogical experiences (total of 09) and were analyzed using mainly content analysis. In the results, we initially found that the teachers' pedagogical actions directed towards doing with few activities that stimulated, in the student, an active learning. Regarding the main types of projects and reflections carried out by teachers about EE, we understand that such practices occurred in conservationist and/or pragmatic dimensions, since they demonstrated a technical and fragmented rationality about the socio-environmental relations that occurred in the region. The same occurred with the characteristics of the Semi-Arid, which were based/oriented on the influences of the “Paradigm of the Drought”, which denoted a simplistic view of reality. However, from constant reflections carried out during the research through participatory and critical-collaborative actions among those involved and from the analysis of the projects developed by the teachers with the students, there was the implementation by the teachers of emancipatory pedagogical practices, compatible with the theoretical assumptions of Critical EE, Education contextualized for living with/in the Semiarid Region and Practical and Critical Rationality. Such practices configure a new context/parameter that can stimulate the resizing of the material conditions that support the Cartesian Paradigm. Finally, aware that other actions and on a continuous basis, with these teachers, are fundamental to consolidate the desired changes, we can conclude that through the analysis of the perceptions and conceptions, of the experiences and projects developed by the teachers together with the students, the continuous training in Critical EA for living with / in the Semi-Arid region provides teachers with theoretical and methodological basement and knowledge for a critical-reflective practice.